Evolution of major histocompatibility complex class I genes in the sable Martes zibellina (Carnivora, Mustelidae). Issue 7 (11th March 2020) - Zhao, Baojun; Zhang, Xue; Li, Bo; Du, Pengfei; Shi, Lupeng; Dong, Yuehuan; Gao, Xiaodong; Sha, Weilai; Zhang, Honghai
Abstract: The molecules encoded by major histocompatibility complex (MHC) genes play an essential role in the adaptive immune response among vertebrates. We investigated the molecular evolution of MHC class I genes in the sable Martes zibellina . We isolated 26 MHC class I sequences, including 12 putatively functional sequences and 14 pseudogene sequences, from 24 individuals from two geographic areas of northeast China. The number of putatively functional sequences found in a single individual ranged from one to five, which might be at least 1–3 loci. We found that both balancing selection and recombination contribute to evolution of MHC class I genes in M. zibellina . In addition, we identified a candidate nonclassical MHC class I lineage in Carnivora, which may have preceded the divergence (about 52 – 57 Mya) of Caniformia and Feliformia. This may contribute to further understanding of the origin and evolution of nonclassical MHC class I genes. Our study provides important immune information of MHC for M. zibellina, as well as other carnivores. Abstract : We investigated the molecular evolution of major histocompatibility complex (MHC) class I genes in the sable Martes zibellina . We found that both balancing selection and recombination contribute to evolution of MHC class I genes in M. zibellina . In addition, we identified a candidate nonclassical MHC class I lineage in Carnivora, which may have preceded the divergence (about 52–57 mya) of Caniformia and Feliformia.